El «Diccionario valenciano» de Josep Pla i Costa: entre la descurança i el purisme - Martines, Josep (Caplletra. Revista Internacional de Filologia, 2015)
The Diccionario Valenciano by Josep Pla i Costa (1817?-1890) is a bilingual Catalan-Spanish Dictionnary left unpublished. The article attempts to outline the main characteristics of this interesting work.